Pengaruh Growth Mindset dan Kecerdasan Spiritual terhadap Hasil Belajar Al Qur'an Hadis Siswa MA Al Ma'had An Nur Bantul - Agustin, Julia; Lina (IIQ An Nur Yogyakarta, 2025)
This study aimed to examine the effects of growth mindset and spiritual intelligence on the Al Qur’an Hadith learning outcomes of students at MA Al Ma’had An Nur Bantul. A quantitative non-experimental method was employed with three variables: growth mindset (X1), spiritual intelligence (X2), and student learning achievement (Y). The sample consisted of 150 tenth-grade students. Data were collected through questionnaires, observations, and documentation. Instrument validity was tested using Aiken’s formula, and reliability was measured by Cronbach’s Alpha. Data analysis involved correlation and multiple linear regression. The results revealed a positive and significant correlation between growth mindset and learning outcomes (r = 0.612; p = 0.000), and between spiritual intelligence and learning outcomes (r = 0.601; p = 0.000). Simultaneously, growth mindset and spiritual intelligence significantly influenced learning outcomes by 53.9%. These findings suggest that enhancing growth mindset and spiritual intelligence can improve students’ achievement in Al Qur’an Hadith learning.